Direct MALDI-TOF MS-based method for rapid identification of microorganisms and antibiotic susceptibility testing in urine specimens - Fouad Assi; Brahim Jabri; Lamia Melalka; Yassine Sekhsokh; Mimoun Zouhdi (Iranian Journal of Microbiology, 2025)
Background and Objectives: Urinary tract infections (UTIs) are considered as a major public health issue, often causing complications. Although the traditional cultivation approach is reliable in diagnosis, it is time-consuming, leading to delay in treatment and contributing to antibiotic resistance due to suboptimal empirical treatments. This study aimed to evaluate the performance of a direct, rapid identification technique using MALDI-TOF MS for pathogen identification and antibiotic susceptibility testing in UTIs, aiming to reduce diagnostic time compared to standard culture methods. Materials and Methods: In the span of a year, 458 monomicrobial urine samples were analysed using both the standard bacterial culture method and the direct MALDI-TOF MS-based method. Antibiotic susceptibility was directly tested on 20 samples using the disk diffusion method. Results: The direct identification technique accurately identified 92.14% of microorganisms at the genus level and 60.92% at the species level within an hour, significantly faster than the 24 to 48 hours required by traditional culture methods. The direct antibiotic susceptibility test results were consistent with the standard post-culture method ranging from 60.00% to 100%. Conclusion: Direct identification using MALDI-TOF MS can improve UTI management by enabling faster pathogen identification and targeted treatments, potentially reducing antibiotic resistance. Further studies are needed in terms of enhancing its clinical utility and reliability.